Culturable bacterial endophytes of Aconitum carmichaelii Debx. were diverse in phylogeny, plant growth promotion, and antifungal potential - Zou, Lan; Wang, Qian; Li, Muyi; Wang, Siyu; Ye, Kunhao; Dai, Wei; Huang, Jing (Frontiers in Microbiology, 2023)
Medicinal plants harbor tremendously diverse bacterial endophytes that maintain plant growth and health. In the present study, a total of 124 culturable bacterial endophytes were isolated from healthy Aconitum carmichaelii Debx. plants. These strains were clustered into 10 genera based on full-length 16S rDNA sequences, among which Bacillus and Pseudomonas were the dominant genera. In addition, A. carmichaelii may capture 10 potential new bacterial species based on multi-locus sequence analysis of three housekeeping genes (gyrA, rpoB, and atpD). The majority of these bacterial endophytes exhibited plant growth-promoting ability through diverse actions including the production of either indole acetic acid and siderophore or hydrolytic enzymes (glucanase, cellulose, and protease) and solubilization of phosphate or potassium. A total of 20 strains inhibited hyphal growth of fungal pathogens Sclerotium rolfsii and Fusarium oxysporum in vitro on root slices of A. carmichaelii by the dual-culture method, among which Pseudomonas sp. SWUSTb-19 showed the best antagonistic activity. Field experiment confirmed that Pseudomonas sp. SWUSTb-19 significantly reduced the occurrence of southern blight and promoted plant biomass compared with non-inoculation treatment. The possible mode of actions for Pseudomonas sp. SWUSTb-19 to antagonize against S. rolfsii involved the production of glucanase, siderophore, lipopeptides, and antimicrobial volatile compounds. Altogether, this study revealed that A. carmichaelii harbored diverse plant growth-promoting bacterial endophytes, and Pseudomonas sp. SWUSTb-19 could be served as a potential biocontrol agent against southern blight.